A cross sectional survey of attitudes, behaviours, barriers and motivators to cycling in University students. (September 2017) - Swiers, Ryan; Pritchard, Catherine; Gee, Ivan
Abstract: High rates of active travel are essential aspects of healthy communities. Increasing cycling participation has the potential to address a range of long-term health and societal issues, and positively contribute to the health and sustainability agenda. Universities have been proposed as appropriate settings for a healthy place approach however, there is a paucity of evidence on student cycling. Therefore the aim of this paper is to explore the motivators and barriers to cycling amongst University students. An online cross sectional survey of young adults (18–25 years) studying at an urban United Kingdom university was undertaken. Using convenience sampling participants were surveyed on levels of cycling (e.g. daily, weekly) alongside perceptions, barriers and motivators to cycling activity. 194 responses were received of which 55% were male, 54% owned a bicycle and 14% were regular cyclists. Cycling motivators were enjoyment and improving fitness; especially amongst regular cyclists. However, weather and safety concerns were the main barriers. The majority (85%) felt more should be done to encourage cycling, with 70% stating cycling was easier 'elsewhere'. Respondents felt cycling had an important environmental element (67%), although less than 8% cited congestion and pollution reduction as a reason for cycling and 64% believed there were more barriers to cycling than driving. This study suggests that levels of cycling within a university setting may be higher than the general population and the appreciation of the merits of cycling are well recognised. In addition motivators and barriers are similar to the wider population. However more research is required, especially with occasional and non-cyclists, to understand how best to address the 'value-action' gap highlighted between cycling attitudes and behaviour amongst university students. Highlights: Primary barriers to cycling are weather and safety across both genders. Considerable heterogeneity exists in general attitudes to cycling. The proportion or regular cyclists was higher than the general population. There were no significant gender differences in relation to cycling frequency. A value-action gap exists regarding environmental factors such as climate change.